Variations in fish body and scale shape among Aphanius dispar (Cyprinodontidae) populations: insights from a geometric morphometric analysis - Khosravi, A. (Caspian Journal of Environmental Sciences, 2017)
Phenotypic variations in fish body and scale shape were investigated among the three populations of Aphanius dispar (Rüppell, 1829) in Southern Iran through the use of landmark-based geometric morphometric analyses. This species is widely distributed in the region, and therefore, considerable morphological variations exist among the geographically allopatric populations. Based on the Principle Component Analysis (PCA), variation in body shape of the females is prominently related to the dorsal fin region, while in the males it is related to the dorsal fin and caudal peduncle. Moreover, the shape variations in the scales are obviously linked to the tip of anterior portion of the scales, and the left and right boundaries between anterior and posterior regions of the scales. The lateral sides of the fish scales in site I are concave, while they are laterally convex in sites II and III. The observed variation seen in the fish body shape and scales among the three studied sites are probably caused by the different ecological conditions of their habitats particularly variation in water flow.